2016
DOI: 10.1371/journal.pcbi.1004942
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Dynamics in MSTd: A Mechanism for Robust Heading Perception Based on Optic Flow

Abstract: Human heading perception based on optic flow is not only accurate, it is also remarkably robust and stable. These qualities are especially apparent when observers move through environments containing other moving objects, which introduce optic flow that is inconsistent with observer self-motion and therefore uninformative about heading direction. Moving objects may also occupy large portions of the visual field and occlude regions of the background optic flow that are most informative about heading perception.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 98 publications
2
49
0
Order By: Relevance
“…Isolating the effect of object speed on heading judgments is difficult because varying the speed of an isolated object will change the duration and timing with which it moves through specific regions of the visual field. Biases in heading perception caused by object motion are well known to depend on starting and ending object position and the temporal profile of the object motion relative to optic flow (19,20,30). Thus, our design employed a multipart object such that it filled the display at all times throughout the trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolating the effect of object speed on heading judgments is difficult because varying the speed of an isolated object will change the duration and timing with which it moves through specific regions of the visual field. Biases in heading perception caused by object motion are well known to depend on starting and ending object position and the temporal profile of the object motion relative to optic flow (19,20,30). Thus, our design employed a multipart object such that it filled the display at all times throughout the trial.…”
Section: Discussionmentioning
confidence: 99%
“…In general, two broad classes of models have been developed to account for heading perception in the presence of moving objects. First, neurally inspired models mimic the response properties of neurons in visual cortex to implement mechanisms such as motion sampling (20), differential motion detection (19,28,29), and competitive dynamics among heading template units (30). The second class of models utilizes features of the visual image to extract heading information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that independently moving objects affected heading judgments only when they obscured or were in close proximity to the FOE of the background optic flow (Layton & Fajen, 2015, 2016a, 2016bRoyden & Hildreth, 1996;Warren & Saunders, 1995). In contrast, Li et al (2018) showed that independently moving objects can affect heading judgments even when they are not close to the FOE of the background optic flow.…”
Section: Experiments 2: Heading Biases When Walkers Are Away From the Foementioning
confidence: 96%
“…Layton and Fajen (2016b) have thus proposed that heading bias produced by object motion may arise from the discrepant optic flow generated within the object and the pseudo-FOE produced at the object's trailing edge. Layton et al have modeled the bias as a peak shift produced by competitive interactions between neural representations of heading in MSTd (Layton & Fajen, 2016a;Layton, Mingolla, & Browning, 2012).…”
Section: Introductionmentioning
confidence: 99%